Leaves contents of nutrients in Cryptostegia madagascariensis in different salinized soils (Research, Society and Development, 2020)
The species C. madagascariensis occurs in humid and arid areas, thus, the species has been standing out as an invasive plant. An experiment was developed in greenhouse with the objective of evaluating the leaf contents (nutritional status) of plants of these invasive plants subjected to different levels of salinity and humidity. The treatments were arranged in randomized blocks, with four repetitions, following the factorial arrangement of 4x4x2, corresponding to the five levels of salinity or incubations (0.3; 1.0; 2.0 and 4.0 dS m-1), four moisture contents (20% of CC; 40% of CC; 70% of CC and 110% of CC) maintained until the end of the test and with two types of soils (Floss Neossol and Vertisolo). Initially, two soils were used, a Floss Neossol and a Vertisol. Leaf samples were analyzed to determine the levels of N, P, K and Na. The soils were placed in pots with a capacity of 21 liters, where each pot contained 19 kg of soil and 4 plants per plot in randomized blocks with 4 repetitions. After elapsed 152 days after sowing, samples of plant tissue (leaves) were taken for chemical analysis. At the end of the experiment, the following leaf variables were carefully evaluated:  Nitrogen (N); Phosphorus (P), Potassium (K+) and Sodium (Na+). The increase in humidity in both soils under growth of young plants increased sodium levels and reduced potassium levels in plant tissue resulting from excess sodium in the two soils as a function of salinity and humidity.